Dydaktyczne koncepcje stylistyki w dwudziestoleciu międzywojennym wobec teorii naukowych = Didactic conception of stylistics in view of scientifical theories between the two world wars - Bogołębska, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the sample of the history of stylistics in Grammar School, as one of the elements teaching literary and linguistic culture. It shows the influence of scientifical and research practice of this discipline on school experience and methodical notions. In the light of didactics of stylistics stressing the content, not the methods and aims of teaching was the characteristic feature of the substantial model dominating then and hence the methodology of theory of literature had the inspiratory rol
Keywords: dydaktyka literatury; dwudziestolecie międzywojenne